2021
DOI: 10.1038/s41398-021-01198-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal acute and chronic inflammation in pregnancy is associated with common neurodevelopmental disorders: a systematic review

Abstract: Inflammation is increasingly recognized as a cause or consequence of common problems of humanity including obesity, stress, depression, pollution and disease states such as autoimmunity, asthma, and infection. Maternal immune activation (MIA), triggered by both acute and systemic chronic inflammation, is hypothesized to be one of the mechanisms implicated in the pathogenesis of neurodevelopmental disorders (NDD). Although there is substantial preclinical evidence to support the MIA hypothesis, the human eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
167
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(180 citation statements)
references
References 82 publications
(175 reference statements)
5
167
2
6
Order By: Relevance
“…The existence of changes within fetal cortex pathways for endogenous antigens (e.g. viral) lends some support the hypothesis that the risk of ASD may be greater among children whose mothers suffered from infectious or immune-related diseases during pregnancy—when the infant brain is developing 60 63 .…”
Section: Discussionmentioning
confidence: 97%
“…The existence of changes within fetal cortex pathways for endogenous antigens (e.g. viral) lends some support the hypothesis that the risk of ASD may be greater among children whose mothers suffered from infectious or immune-related diseases during pregnancy—when the infant brain is developing 60 63 .…”
Section: Discussionmentioning
confidence: 97%
“…In fact, FKBP51 has been shown to moderate immune pathways [ 49 ] via for example direct interaction with regulators of the alternative NFkappaB pathways leading to a proinflammatory immune response [ 50 ]. This is of interest, given the fact that long-term effects of BET have been associated with childhood mental and behavioral disorders [ 18 ] and that maternal inflammation has indeed been suggested as possible mediator between maternal stress and offspring neuropsychiatric risk [ 51 , 52 ]. This may extend to placental inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] Han et al demonstrated that maternal inflammatory states were linked with neurodevelopmental disorders, including ASD. [ 18 ] Therefore, dysfunctional immune defenses and inflammatory reactions in children with ASD could be important precipitating factors for triggering this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in this study are consistent with those reported by Zerbo et al, [ 22 ] who showed that compared with healthy children, children with ASD showed increased serum MCP-1 levels and decreased RANTES levels. In addition, Han et al [ 18 ] documented that the levels of MCP-1 and RANTES in children with ASD were significantly higher than those in normally developing children, whereas the levels of IL-8, IP-10, and MIG are significantly lower in autistic children than in normal children. The variations in IL-8, IP-10, and MIG levels are consistent with the results of our study; however, the result of the RANTES level is contrary to our findings.…”
Section: Discussionmentioning
confidence: 99%